1999
DOI: 10.1007/pl00015012
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Bacterial Infection During Management of Open Leg Fractures

Abstract: In a randomised double-blind trial conducted between 1990 and 1994, 616 patients from 43 centres, pefloxacin (group P, 316 patients) and a cefazolinoxacillin combination (group C, 300 patients) were compared in the prophylaxis of bone infection after grade 1 and 2 open leg fractures. Samples were obtained at emergency, before and during surgery, and from drain aspirates. Antimicrobial susceptibility, slime production and adherence properties of the bacteria were tested. Cultures at emergency and before surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 13 publications
5
84
0
8
Order By: Relevance
“…In randomized studies, the incidence of infection after intramedullary fixation of closed tibial fractures reached 1.3% (95% CI 0.3-7.1%); in a meta-analysis, no difference could be found between reamed and unreamed nailings (risk ratio [RR] 0.98, 95% CI 0.21-4.76, risk difference [RD] -0.4%, 95% CI -3-2%) [1]. As it has to be expected, the incidence of infection after open injuries is higher (7.3%, 95% CI 5.4-9.7%) [2].…”
Section: Introductory Remarksmentioning
confidence: 76%
See 1 more Smart Citation
“…In randomized studies, the incidence of infection after intramedullary fixation of closed tibial fractures reached 1.3% (95% CI 0.3-7.1%); in a meta-analysis, no difference could be found between reamed and unreamed nailings (risk ratio [RR] 0.98, 95% CI 0.21-4.76, risk difference [RD] -0.4%, 95% CI -3-2%) [1]. As it has to be expected, the incidence of infection after open injuries is higher (7.3%, 95% CI 5.4-9.7%) [2].…”
Section: Introductory Remarksmentioning
confidence: 76%
“…Nach offenen Verletzungen liegen die Infektionsraten erwartungsgemäß höher (7,3%, 95%-CI 5,4-9,7%) [2]. Aus Fallserien der Jahre 1943-1979 wurden von 23 538 Patienten kumulative Inzidenzen zwischen 0,2% (95%-CI 0,0-0,5%) und 17,7% (95%-CI 0,0-35,8%) berichtet [22].…”
Section: Figureunclassified
“…and Klebsiella spp. (Hirsch and Smith 1978 (Calza et al 2001) and also Pseudomonas aeruginosa (Carsenti-Etesse et al 1999, Greenberg et al 2000, Calza et al 2001, S hirliff et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…The question was whether use of negative pressure wound therapy beyond 72 hours would result in increased infection rates compared with historic controls [1,11,13,20,26,28]. Reported infection rates are highly variable for Grade IIIB tibia wounds with the upper end at 67% [10]. Eight [15,16,30,33,35,36,47,50] of the 10 studies with data regarding extended use of negative pressure wound therapy reported infection rates comparable to historic rates or lower.…”
Section: Does Negative Pressure Wound Therapy Facilitate Late Flap Prmentioning
confidence: 99%
“…The implant used for bony stabilization may compromise regional bone blood flow and may lead to wound problems [55]. These factors and others contribute to wound-bed bacterial colonization [10,12,14,27,46,54,55] and progression to infection. Since Godina's study [25], it generally has been accepted that these open fractures require early (within 72 hours) bony stabilization and soft tissue reconstruction.…”
Section: Introductionmentioning
confidence: 99%